Judiciary and Arbitration in Bahrain : A Historical and Analytical Study - Radhi, Hassan Ali (Brill Book Archive Part 1, ISBN: 9789004472495., 2003)
Although Bahrain has had an established system of law courts since 1771, it was only in the course of the twentieth century that it gradually developed a fully-fledged legal system compatible with international norms. Today, like the other Gulf states, its sophisticated judiciary represents a blend of Islamic Shari'a, British common law, and modern reforms drawn principally from Egypt's civil law-influenced trdition. In recent decades, arbitration has also taken its place as an important adjunct to the judiciary.